Kompetensi Kultural Pendidik Anak Usia Dini - Luluk Iffatur Rocmah (Proceedings of The ICECRS, 2019)
This study is a descriptive qualitative research. This research aim to analyze and express cultural competence among early childhood teachers in Sidoarjo. Data collection was done by observation, interview and documentation. The subjects in this study were early childhood teachers in Sidoarjo from both homogeneous and heterogeneous schools. This study resulted the findings that educators can be competent in culturally diverse classroom teaching, he must have a cultural component of cultural awareness, cultural knowledge, cultural attitudes and cultural skills. Cultural awareness and cultural attitudes can be developed through cultural experience or cross-cultural interaction. While cultural knowledge can be developed through training such as workshops, seminars, conferences etc. And cultural teaching skills can be developed through teaching experience.